Centipeda minima Extract Attenuates Dextran Sodium Sulfate-Induced Acute Colitis in Mice by Inhibiting Macrophage Activation and Monocyte Chemotaxis - Chan, Brandon Dow; Wong, Wing-Yan; Lee, Magnolia Muk-Lan; Leung, Tsz-Wing; Shum, Tan-Yu; Cho, William Chi-Shing; Chen, Sibao; Tai, William Chi-Shing (Frontiers in Pharmacology, 2021)
Inflammatory bowel disease (IBD) is an idiopathic inflammatory disease affecting the gastrointestinal tract. IBD is characterized by courses of relapse and remission, and remains incurable. Although multiple factors are related to the pathogenesis of IBD, disruption of intestine mucosal homeostasis has been proposed to be a major contributor to IBD, and abnormal activation of immune cells is key for initiation of the inflammatory response. Among immune cells, macrophages are the most abundant cells in the intestine. Once activated, they are responsible for secretion of pro-inflammatory cytokines and chemokines to attract circulating monocytes to the inflammatory site, exacerbating the inflammatory response, and finally leading to tissue damage. Therefore, suppression of activated macrophages, inhibition of cytokine and chemokine production and subsequent monocyte chemotaxis possesses great potential for the treatment of IBD. In our study, we have demonstrated the suppressive effect of total extract of Centipeda minima (CME) on the activation of NF-κB, STAT3, and MAPK signaling in LPS-stimulated RAW264.7 macrophages. In addition, we identified the significant suppressive effect of CME on CCL8 expression in activated macrophages, which potentially contributed to inhibition of monocyte chemotaxis. In the DSS-induced acute colitis mouse model, we have demonstrated the suppressive effect of CME on intestinal macrophage infiltration and its therapeutic effect in IBD. Altogether, we have provided evidence of the therapeutic effect of CME in IBD and the potential of CME for use in the treatment of IBD.